The Role of Mobile Social Media in Enhancing University Students’ Teaching-Learning Process - Mujica Paredes, Abel-Enrique-Jesús (2026)
The main objective of this research is to determine the influence of social media on the teaching-learning process in university students and whether social networks enable knowledge sharing in their teaching-learning process. The methodology used is descriptive and quantitative, quantifiable information has been collected for analysis through an online questionnaire, whose population are university students in the province of Abancay, with a representative sample of 1009 students. The results are: the continued use of internet and social networks mainly by students, who use it to relate academically and socially with students from different parts of the world, the statistical part of the combinatorial factor analysis obtained values such as Cronbach’s Alpha (0. 935) and McDonald’s Omega (0.934), both higher than 0.7, which is the statistical value of the original instrument, while the exploratory factor analysis, for which a “Varimax” rotation was defined corrected the results of the factor analysis. Concluding that each factor significantly influences the teaching-learning process, as well as there is a causal relationship between student engagement and reputation in the dimensions of knowledge sharing and knowledge formation. Thus we can affirm that the most time spent accessing the internet is at home and followed by the university due to the free Wi-Fi.